2019
DOI: 10.1002/ijc.32415
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of nuts and seeds and pancreatic ductal adenocarcinoma risk in the European Prospective Investigation into Cancer and Nutrition

Abstract: Four epidemiologic studies have assessed the association between nut intake and pancreatic cancer risk with contradictory results. The present study aims to investigate the relation between nut intake (including seeds) and pancreatic ductal adenocarcinoma (PDAC) risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. Cox proportional hazards models were used to estimate hazards ratio (HR) and 95% confidence intervals (95% CI) for nut intake and PDAC risk. Information on intake of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Some epidemiological studies showed that Mediterranean diet consisting of good amounts of vegetables, especially tomato, fruits, olive oil, grains, and fish, might contribute to lower rates of cancer. [31][32][33] LYC is a major component in tomato and is also abundantly found in various fruits and vegetables. 34 It acts as a potential chemoprotective agent against several types of cancers with minimum toxicity to normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some epidemiological studies showed that Mediterranean diet consisting of good amounts of vegetables, especially tomato, fruits, olive oil, grains, and fish, might contribute to lower rates of cancer. [31][32][33] LYC is a major component in tomato and is also abundantly found in various fruits and vegetables. 34 It acts as a potential chemoprotective agent against several types of cancers with minimum toxicity to normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…An inverse association between nut consumption and cancer was found for colorectal cancer for the ≥3 servings per week group vs. none (for women: adjusted ORs: 0.30, 95% CI 0.15-0.60; for men: adjusted ORs: 0.28, 95% CI 0.17-0.47) [195]. Decreased rates associated with nut consumption, even if not significant, were reported in relation to pancreatic cancer (highest intake vs. non-consumers: HR: 0.89, 95% CI 0.72-1.10) in the European Prospective Investigation into Cancer and Nutrition (EPIC) study with 476,160 participants and mean follow-up of 14 years [196]. These findings encourage the preference for plant sources of fat.…”
Section: Mufasmentioning
confidence: 94%
“…Subsequently, a study from the Netherlands of 120,852 men identified 583 cases of pancreatic cancer and came to the same conclusion [49]. Culminating in the largest epidemiological study to look specifically at the role of nuts in pancreatic cancer incidence, the European Prospective Investigation into Cancer and Nutrition (EPIC) study, which identified 1283 patient with pancreatic ductal cancer in a population of over 400,000 people [50]. This final study was not able to conclusively identify a beneficial role of high nut consumption in the prevention of pancreatic cancer.…”
Section: Nutsmentioning
confidence: 83%